(untitled) (Research, Society and Development, 2020)
Falls are considered a public health problem in Gerontology, given its prevalence and consequence for the health of the elderly. Preventive measures based on educational activities aim to improve the health and quality of life of the elderly who may be exposed to falls in their homes. The present study aims to investigate the knowledge of the elderly about the theme of prevention of home falls from an educational activity using booklet, model, error games and puzzle. An exploratory and descriptive study with a quantitative approach was carried out in a school clinic of a higher education institution located in the city of Fortaleza. The population of this study was composed of 37 elderly people assisted by Physiotherapy, aged 60 years or over. The final sample consisted of 10 elderly people (28% of the population in which educational games were held. The educational intervention was carried out in an average time of 30 minutes, in a conversation about home risks, plus an explanation of the booklet, model and pictures. The results obtained through the check list, inferred that 100% (N = 10) of the elderly identified the risks inherent in the The study brought positive results related to satisfaction and motivation to participate in the educational activity with the use of error games and puzzles. The knowledge acquired by the elderly was perceived by the researcher with great efficiency through the information cited about the risks of falls and their prevention.